Comparison of the Surgical Outcomes of Free Flap Reconstruction in Head and Neck Cancer Patients - Mehreen Babar, Fatima Usman, Wajih Ud Din Shinwari, Sajid Rashid Nagra, Salman Aftab Ahmed, Khurram Nadeem (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The goals of this research were to (1) assess the efficacy of free flap reconstruction in patients with early and recurrent head and neck cancers, and (2) investigate the variables associated with these surgeries that increase the risk of problems. Study Design: Retrospective Study Place and Duration: Frontier Medical College, Abbottabad, from March, 2022 to August, 2022. Methods: Total 200 patients of head and neck cancer were included in this study. Patients were both males and females with primary and recurrent cancer types were underwent for free flap reconstruction. After receiving informed written consent, in-depth demographic information about the cases that were enrolled was recorded. Patients were divided in two groups. Hundred patients of recurrent cancers were included in group I and 100 patients of primary cancers were included in group II. Surgical outcomes among both groups were assessed and compared. SPSS 24.0 was used to analyze all data. Results: We found that 87 (87%) patients in group I and 81 (81%) patients in group II were males. Mean age of the patients in group I was 49.8±11.37 years and in group II mean age was 51.4±7.42 years. Majority of the patients had tumor stage 5. Smoking, betel nut and alcohol were the most common causes found in all cases. Anterior lateral thigh (ALT) and anterior medial thigh (AMT) were the most common flap types among both groups. We found that free flap reconstruction had higher success rate in primary cancers found in 96 (96%) as compared to recurrent cancers group in 92 (92%). There was no any significant difference found among both groups in terms of post-surgery complications. Conclusion: This study’s findings suggest a greater failure rate for free flap reconstruction in the recurrent group compared to the primary group, however this finding may be attributable to the varied patient characteristics between the two groups.